The Company town : architecture and society in the early industrial age - Garner, John S., 1945- (Oxford University Press, 1992)
Company towns - those associated with textiles, mining, or tool manufacturing, for example - can be found worldwide and from antiquity to the present. But with the Industrial Revolution what had been the isolated incidence of such towns became a building phenomenon. This book describes and compares in seven essays the concurrent development and building of selected towns in Europe and the Americas.